2003
DOI: 10.1243/09544070360692032
|View full text |Cite
|
Sign up to set email alerts
|

The optimization of electric power assisted steering to improve vehicle performance

Abstract: To investigate the e ects of electric power assisted steering ( EPAS ) on a vehicle's steering performance, this paper explicitly proposes several indices, such as steering sensitivity and road feel, for evaluation of steering performance. Then a single-track car model with lateral and yaw movement is considered and an EPAS model is built. The mathematical expressions for the steering performance indices are deduced and a stability criterion is established by integrated analysis of the vehicle's dynamics and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This chapter based on artificial immune system with the pavement impact compensation control strategy, but the basic idea of literature from control of the RTSS estimation method [3]. In order to research the EPS in the pavement shock signal under all the performance of interference, the need for research, first to fix the steering wheel, the simplified model for EPS at this time [5]:…”
Section: Impact Compensation Control Strategy Of Eps Based On Aismentioning
confidence: 99%
“…This chapter based on artificial immune system with the pavement impact compensation control strategy, but the basic idea of literature from control of the RTSS estimation method [3]. In order to research the EPS in the pavement shock signal under all the performance of interference, the need for research, first to fix the steering wheel, the simplified model for EPS at this time [5]:…”
Section: Impact Compensation Control Strategy Of Eps Based On Aismentioning
confidence: 99%
“…The authors of article [8] proposed two indicators -steering sensitivity and road feel -in order to assess the performance of the steering system. It was found that steering sensitivity depends on the following factors: stiffness of the torque sensor, the electrical characteristics of the propulsion engine, its moment of inertia, the transmission ratio of the power steering, the boost control and the vehicle parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Great progress has been made in the control system of EPS developing and designing, but few discussions have been made on the research and optimization of the parameters on the vehicle controllability and stability. Liu, et al [7] analyzed the influence of some parameters of EPS, but the effect of other parameters, including the inductance, the torque constant and resistance of the motor, on steering sensitivity and road feel have not been studied. To design and improve the EPS system performance, it is necessary to study the parameters of the EPS system further.…”
Section: Introductionmentioning
confidence: 99%